Investigations of the vascular endothelial factor levels’ changes in experimental diabetic retinopathy - Preys, Nataliya; Savytskyi , Ivan (Journal of Education, Health and Sport, 2022)
Introduction: The paper presents the results of the vascular endothelial growth factor of rats with experimental diabetic retinopathy (DR). Material and methods: Experimental studies were performed on white Wistar rats, which were divided into 7 groups: 1st group – intact animals; 2nd group – 60 animals with modelling of DR without correction (control pathology); 3rd group –60 animals with modelling of DR with correction of hyperglycemia; 4th group – 60 animals with modelling of DR with correction of hyperglycemia, administration of aflibercept and L-arginine solution; 5th group – 60 animals with modelling of DR with correction of hyperglycemia, administration of aflibercept and bromfenak; 6th group – 60 animals with modelling of DR with correction of hyperglycemia, administration of aflibercept, L-carnitine solution and bromfenak; 7th group – 60 animals with modelling of DR with correction of hyperglycemia, administration of aflibercept, L-arginine solution and citicoline. Results: The results of the analysis of the VEGF in the 2nd group confirm the development of DR, a particularly pronounced increase in the marker was detected on the 180th day of the development of the pathological process. The results of the 4th group indicate that the involvement of a nitric oxide donor and aflibercept in the correction of DR has positive effect on the reduction of the VEGF level, more pronounced compared to the 3rd group, but it does not reach normative values. It is observed that the correction of the simulated pathological condition by reducing hyperglycemia, administration of aflibercept and bromfenac (group No. 5) gives positive results, but less pronounced, compared to the data of the 4th group. It was found that in rats with DR with subsequent correction of hyperglycemia, administration of aflibercept, L-carnitine and bromfenac (group No. 6) at the first stage, there is a pronounced effectiveness of the proposed method of correction in comparison with the previously considered methods. The most pronounced positive effect of normalizing the VEGF level is observed when using a hypoglycemic drug in combination with the administration of aflibercept, a solution of L-arginine and citicoline (group No. 7). Conclusions: The obtained data confirm the development of diabetic retinopathy, a particularly marked increase in the marker was detected on the 180th day of the development of the pathological process (p<0.001). Aflibercept has a positive effect on the normalization of this condition, but a more pronounced effect is observed in combination with long-term administration of L-arginine. The relationship between the normalization of the vascular growth factor and the correction of hypoxia was also revealed.